Arsenic (V) removal from aqueous solutions using natural clay ceramic monoliths. Issue 11 (2nd November 2019) - García-Carvajal, C.; Villarroel-Rocha, J.; Curvale, D.; Barroso-Quiroga, M. M.; Sapag, K.
Abstract: An adsorbent material arranged in a ceramic monolith (CM) obtained by extrusion technique using natural bentonite and alumina (as raw materials) is presented. Ceramic and raw materials were characterized by X-ray fluorescence, thermal analysis, X-ray diffraction, and textural analysis (with N2 adsorption–desorption at 77 K and Hg intrusion–extrusion porosimetry) to determine their chemical and physical properties. Then, As (V) adsorption capacity of the CM at different pH (3–9) using arsenic aqueous solution (with 2000 µg As (V) L −1 ) was evaluated. Additionally, studies of kinetics and equilibrium of As (V) adsorption on CM were performed. It was found that: (i) the As (V) removal capacity is favored at acidic pH, reaching an average value of 15 µg As (V) per gram of CM; (ii) from kinetic studies, As (V) adsorption on CM occur in two stages, the first of them reaching a lower As uptake in a short time period, followed by an slow second stage with a subsequent higher As uptake, which continued for a longer time period, reaching equilibrium conditions in approximately 24 h; and (iii) the As (V) adsorption isotherm is a type-Langmuir, indicating that the CM present an homo quantity of fixed sites to adsorb the As (V).